2020
DOI: 10.1007/978-3-030-32053-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Data Analysis: A New Method for the Study of Personality and Health

Abstract: A majority of research by personality psychologists examining health has utilized publicly available datasets, for good reason. These resources are often the only available datasets large enough to detect expected effect sizes and may contain biological or genetic data that is difficult to obtain. However, researchers tend to examine only one large dataset at a time. Given recent meta-research on the robustness and replicability of "established" findings, all researchers should take greater care to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…One goal of this project was to apply techniques designed to enhance replicability of results to longitudinal research on personality development across adulthood using existing data. Researchers across many fields are currently focused on enhancing replicability and reproducibility, and encouraging open science practices (Condon et al, 2017; Nelson, Simmons, & Simonsohn, 2018; Vazire, 2018; Weston, Graham, & Piccinin, 2019). However, many of the shifts in research practices have focused on experimental sub‐fields of psychology, leaving longitudinal researchers with more limited options regarding how to enhance the replicability of their findings.…”
Section: Methodsmentioning
confidence: 99%
“…One goal of this project was to apply techniques designed to enhance replicability of results to longitudinal research on personality development across adulthood using existing data. Researchers across many fields are currently focused on enhancing replicability and reproducibility, and encouraging open science practices (Condon et al, 2017; Nelson, Simmons, & Simonsohn, 2018; Vazire, 2018; Weston, Graham, & Piccinin, 2019). However, many of the shifts in research practices have focused on experimental sub‐fields of psychology, leaving longitudinal researchers with more limited options regarding how to enhance the replicability of their findings.…”
Section: Methodsmentioning
confidence: 99%
“…cohort samples in a pooled analysis allows for more robust and replicable results (Hofer & Piccinin, 2009;Weston et al, 2020) because the associations are tested across samples that differ in age, nationality, and measures of IADLs/ADLs and personality. Eight samples were identified that were comparable in overall design, with personality traits and IADLs/ADLs assessed at baseline, and IADLs/ADLs assessed again years later.…”
mentioning
confidence: 99%
“…A key consideration during this phase is the complexity of the research question being posed. As we suggest in Weston, Graham, and Piccinin (2019) it is often best to choose a simple yet foundational question. With complex questions and models that are increasingly common in aging research, many datasets are unlikely to fulfill highly specialized variable, design, or data requirements required to test them (Kelly et al, 2016).…”
Section: Phase 1: Define the Research Question And Conduct A Literature Searchmentioning
confidence: 99%
“…Lifespan development, health psychology, and aging are cases in point: replication is a core scientific value, yet, replications are difficult to accomplish where complex longitudinal or timeintensive data are needed (Hofer & Piccinin, 2009, 2010Piccinin & Hofer, 2008;Weston, Graham, & Piccinin, 2019) or where participants are followed for long periods until a certain event occurs such as onset of a disease, a relationship event (like divorce), or death. Thus, fields that rely heavily on long-term longitudinal data, such as aging research, lifespan development, some subareas of health psychology, behavioral and social epidemiology, and others, face unique challenges when trying to adopt open, reproducible, and replicable research practices.…”
Section: Introductionmentioning
confidence: 99%